Remarks at the 2014 Prince Mahidol Award Conference, Pattaya, Thailand, January 29, 2014 - Kim, Jim Yong (2016)
Jim Yong Kim, President of the World Bank Group, said he was honored to share the Prince Mahidol award with a distinguished group of individuals who have spent many years fighting to end the HIV-AIDS epidemic. He said that Thailand was the first developing country to mount a successful HIV prevention response. Thailand’s successes in AIDS prevention and treatment were not inevitable, neither was its quest for universal health coverage. He have learned that investing in people is not just the right moral choice, ambitious reforms require skillful balancing of competing demands and a handful of committed people with vision have the power to change the world. He concludes that lessons are universal and timeless that we can achieve great things, if we learn from history, and contribute to a lasting evidence-based wisdom.